CORRELATION BETWEEN THE AMOUNT OF ORGANIC MATTER AND THE ABUNDANCE OF MACROZOOBENTHOS IN THE COASTAL WATERS OF DUMAI CITY - Octalina, Fazrianty; Badrun, Yeeri; Retnawaty, Sri Fitria (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This research was conducted in March 2022 in the Coastal Waters of Dumai City. Thisstudy aims to analyze the amount of organic matter and the abundance of macrozoobenthosand the relationship between the amount of organic matter and the abundance ofmacrozoobenthos. The method used is a survey method consisting of 10 stations with 2replications at each station. And 1 station is a control station located on the north coast ofNorth Rupat District, Bengkalis Regency. Sediment sampling was carried out in the field andthen taken to the Marine Chemistry Laboratory, Riau University for analysis of organic matterand macrozoobenthos analysis. Based on a simple linear regression test, the relationshipbetween the amount of organic matter and the abundance of macrozoobenthos obtained acorrelation value (r) = -0. 4637 with the mathematical equation y = -4.884x + 98.896. The testresults show a weak and inverse relationship between the amount of organic matter and theabundance of macrozoobenthos. This means that with the increase in the amount of organicmatter, the abundance of macrozoobenthos in the coastal waters of Dumai City will decrease.The value of the coefficient of determination (R2) is 0.2146. This figure shows that the effectof organic matter on the abundance of macrozoobenthos is small, namely 21.46%.